Pemanfaatan Komposter Sebagai Solusi Berkelanjutan Dalam Pengelolaan Sampah Organik Di Kelurahan Bandengan, Kota Pekalongan - Muhammad Al Ghifari; Mohammad Hamam; Moch Izzul Haq Amien; Nuha Kamilah; Cantika Prameswari Fourin; Nur Khabibah; Calvin Ardiansyah; Nency Oktavia Angelita; Laelia Safitri; Nesa Anggun Meria; Kurnia Lingga Andini; Candra Dwi Pradana (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
The increasing volume of household organic waste in urban residential areas has become a serious environmental challenge, including in Bandengan Subdistrict, North Pekalongan, Pekalongan City. Organic waste originating from kitchen residues dominates daily waste generation and, if improperly managed, contributes to environmental pollution and greenhouse gas emissions. This community service activity aimed to enhance environmental awareness and community participation through the utilization of household-scale composters as a sustainable solution for organic waste management. The program was implemented through the Kuliah Kerja Nyata (KKN) program of Universitas Pekalongan using a participatory approach that included observation, environmental education, hands-on training in compost bin construction and usage, as well as mentoring and evaluation. The results indicate an increase in community knowledge, skills, and active involvement in processing organic waste independently. The application of drum-based composters proved effective in reducing organic waste volume and fostering environmentally responsible behavior. This activity demonstrates that community-based composting supported by practical education can serve as an effective and sustainable strategy for urban organic waste management.